DISTRIBUTION OF CARBON MONOXIDE (CO) IN TITAN'S ATMOSPHERE FROM ALMA OBSERVATION - FAJRINA -10314009 , RIZKI
Titan is the largest moon of Saturn and the only natural satellite that has atmosphere. The Voyager 1 mission in 1980 has revealed that the atmosphere of Titan was dominated by nitrogen (N2), more than 95%, followed by methane (CH4) about 3–4%, and contained various minority compounds such as hydrocarbons, nitriles, and oxygen-bearing compound. Titan's atmosphere is the place where photochemical processes occur and produce complex organic compounds. This Final Project focus on the distribution of one of the most abundant molecules on Titan, carbon monoxide (CO). The first detection of CO was made by Lutz et al. in 1982 at Kitt Peak National Observatory. Since then, the origin of CO was modeled by Yung et al. (1984) and predicted that this molecule must be distributed uniformly in Titan’s atmosphere. In this Final Project, we use selected data obtained by ALMA (Atacama Large Millimeter/Submillimeter Array) to analyze the distribution of CO both vertically in the atmosphere and spatially in Titan’s disk since it is spatially resolved. Images of Titan from band 7 and 9 of ALMA can be produced as well as spectra of CO in the corresponding bands. The disk averaged spectra of CO is analyzed using radiative transfer calculations and is compatible with a uniform vertical profile of CO assuming an abundance of 5,0 × 10-5 and the Huygens thermal profile of Titan. Although Titan’s disk is successfully resolved, various factors must be considered to derive its distribution and needs further analyses.